Characterization of an O-Demethylase of Desulfitobacterium hafniense DCB-2 - Studenik, Sandra (American Society for Microbiology, 2012)
Besides acetogenic bacteria, only Desulfitobacterium has been described to utilize and cleave phenyl methyl ethers under anoxic conditions; however, no ether-cleaving O-demethylases from the latter organisms have been identified and investigated so far. In this study, genes of an operon encoding O-demethylase components of Desulfitobacterium hafniense strain DCB-2 were cloned and heterologously expressed in Escherichia coli. Methyltransferases I and II were characterized. Methyltransferase I mediated the ether cleavage and the transfer of the methyl group to the superreduced corrinoid of a corrinoid protein. Desulfitobacterium methyltransferase I had 66% identity (80% similarity) to that of the vanillate-demethylating methyltransferase I (OdmB) of Acetobacterium dehalogenans. The substrate spectrum was also similar to that of the latter enzyme; however, Desulfitobacterium methyltransferase I showed a higher level of activity for guaiacol and used methyl chloride as a substrate. Methyltransferase II catalyzed the transfer of the methyl group from the methylated corrinoid protein to tetrahydrofolate. It also showed a high identity (∼70%) to methyltransferases II of A. dehalogenans. The corrinoid protein was produced in E. coli as cofactor-free apoprotein that could be reconstituted with hydroxocobalamin or methylcobalamin to function in the methyltransferase I and II assays. Six COG3894 proteins, which were assumed to function as activating enzymes mediating the reduction of the corrinoid protein after an inadvertent oxidation of the corrinoid cofactor, were studied with respect to their abilities to reduce the recombinant reconstituted corrinoid protein. Of these six proteins, only one was found to catalyze the reduction of the corrinoid protein.